Recent Query Reformulation Approaches for Information Retrieval System - A Survey - Gupta, Vishal; Dixit, Ashutosh (Recent Advances in Computer Science and Communications, 2023)
Around trillions of data are uploaded to the internet every year. Extracting useful information using only a few keywords has become a major challenge. The field of Query Reformulation (QR) is focused on the efficient retrieval of information to overcome this. It is widely used in the domain of information retrieval (IR) and related fields such as search engines, multimedia IR, cross-language IR, recommender systems, and so on. Query reformulation techniques incur extra computational costs. Due to this reason, the use of query reformulation techniques is sometimes prohibited in internet searches as searching over the internet requires a fast response time. But due to the success of NLP (Natural Language Processing) using machine learning/deep learning in recent years, there has been a boom of study in this area. In this literature, a variety of term selection, term extraction, and query reformulation strategies based on recent technologies used by researchers have been presented, necessitating a wide survey to focus research in this promising area. Recent QR approaches and the datasets, techniques, and evaluation metrics used in this paper will help researchers understand and focus more on research in this promising area so that a better solution will be proposed. From the survey, it may be observed that one of the hottest subjects in the field of IR right now is applying deep learning to IR systems for query reformulation.
Keywords: term extraction